Crystal structure of 1,3-bis(2,6-diisopropylphenyl)-4,5-dimethyl-1H-imidazol-3-ium bromide dichloromethane disolvate - Matthias Berger; Norbert Auner; Michael Bolte (Acta Crystallographica Section E, 2014)
The title solvated salt, C29H41N2+·Br−·2CH2Cl2 was obtained from the reaction of the Arduengo-type carbene 1,3-bis(2,6-diisopropylphenyl)-1,3-dihydro-4,5-dimethyl-2H-imidazol-2-ylidene with Si2Br6 in dichloromethane. The complete cation is generated by a crystallographic mirror plane and the dihedral angle between the five-membered ring and the benzene ring is 89.8 (6)°; the dihedral angle between the benzene rings is 40.7 (2)°. The anion also lies on the mirror plane and both dichloromethane molecules are disordered across the mirror plane over two equally occupied orientations. In the crystal, the cations are linked to the anions via C—H...Br hydrogen bonds.